Influence of propylene units stereoregularity in modified ethylene–propylene–diene elastomers on the ozone resistance of covulcanizates with acrylonitrile-butadiene rubbers - Livanova, Nadezhda; Popov, Anatoliy; Shershnev, Vladimir; Zaikov, Gennady (Lviv Politechnic Publishing House, 2017)
Показано, що модифікування етилен-про- пілен-дієнових еластомерів при додаванні фрагментів приско- рюючої речовини для поліпшення їх сумісності з акрилонитрил- бутадієновими каучуками і зменшення швидкості розкладу озону є ефективним тільки у випадку низької стереорегуляр- ності пропіленових ланок у кополімері етилен-пропілен-дієн, коли зшиту систему додають до акрилонітрил-бутадієнового каучуку. Визначено, що при високій ізотактичності пропі- ленових фрагментів в ланцюзі етилен-пропилен-дієнових елас- томерів їх модифікація знижує озоностійкість зшитих струк- тур незалежно від режиму введення структуруючих систем.

1The modification of ethylene–propylene–diene elastomers via the addition of fragments of an accelerating agent to improve their compatibility with acrylonitrilebutadiene rubbers and to reduce the rate of ozone degradation of the polydiene matrix is efficient only in the case of low stereoregularity of propylene units in the ethylene–propylene–diene copolymers when the crosslinking system is added to acrylonitrile-butadiene rubber. When the isotacticity of propylene fragments in the chains of ethylene–propylene–diene elastomers is high, their modification leads to a reduction in the ozone resistance of the crosslinked blend independently of the mode of introduction of the crosslinking system.
Вплив стереорегулярності пропіленових ланок в модифікованих етилен-пропілен-дієнових еластомерах на озоностійкість ко-вулканізатів з акрилонітрил-бутадієновими каучуками
Keywords: акрилонітрил-бутадієновий каучук; етилен-пропілен-дієновий еластомер; озон-індукований роз- клад; сумісність; структура міжфазових шарів; пропіленові ланки; стереорегулярність; acrylonitrile-butadiene rubber; ethylene– propylene–diene elastomer; ozone-induced degradation; compatibility; interphase layers structure; propylene units; stereoregularity